The creation of an adaptable informed consent form for research purposes to overcome national and institutional bottlenecks in ethics review: experience from rare disease registries - Landi, Annalisa; Mimouni, Yanis; Giannuzzi, Viviana; Schaefer, Franz; Altavilla, Annagrazia; Gibson, Spencer; Julkowska, Daria (Frontiers in medicine, 2024)
Background: The lack of harmonization of evaluation criteria by Ethics Committees in the European Union (EU) has led to inconsistent ethics reviews received by research sites participating in multicenter non-interventional studies. The European General Data Protection Regulation (GDPR) appears to be implemented at national level with a substantial degree of variance in interpretation. The European Reference Networks (ERNs) were struggling in setting an Informed Consent Form (ICF) for registries, allowing reuse of data for research purposes. The aim of this work is to develop an adaptable ICF for research purposes to be used in ERN registries. Methods: To work on this challenge, a team was established within the European Joint Programme on Rare Diseases (EJP RD) to develop a patients’ registry ICF template allowing easy adaptation to ERNs, country, and site-level specificities. ERN and patients’ representatives validated the choice of developing a GDPR-compliant template for research purposes. The feedback received from 34 Ethics Committees on the Clinical Patient Management System ICF, including the submission of patients’ data to the ERN registries and the EU consent regulatory framework were analyzed along with existing ontologies for data access and reuse. An adaptable ICF was developed following iterative cycles of consultation and review by clinicians, research experts, ethics and regulatory advisors, and patients’ representatives. The development of pediatric material for minor participants was also undertaken. Results and Conclusion: Research oriented ICF templates for adults and for parents/legal representatives of patients were released in 26 national languages. This adaptable ICF aims to foster, according to patients’ preferences, the reuse of registries data for research purposes in compliance with the applicable laws and standards. Pediatric material is being finalized to collect minors’ assent. ICF machine-readability is also progressing to enhance data discovery and facilitate its access and reuse conditions.
Gesehen am 22.10.2024